Ransacking Paris - Miller, Patti, 1954- (University of Queensland Press, 2015)
When Patti Miller arrives in Paris to write for a year, the world glows as if the light that comes after the sun has gone down has spilled gold on everything. But wasn't that just romantic illusion? Miller grew up on Wiradjuri land in country Australia where her heart and soul belonged. Mother of grown-up boys with lives of their own, what did she think she would find in Paris that she couldn't find at home? She turns to French writers, Montaigne, Rousseau, de Beauvoir, and other memoirists, each one intent on knowing the self through gazing into the looking glass of the great world. They accompany her as she wanders the streets of Paris, they even have coffee together, and they talk about love, suffering, desire, motherhood, truth-telling, memory, the writing journey, and how to know who we are in the family and in the cultures that shape us. This story, of a year spent writing and reading in Paris, explores truth and illusion, self-knowledge and identity, and evokes the beauty, the contradictions and the daily life of contemporary Paris.